Studi Kualitatif Tentang Solusi Al-Qur’an Terhadap Konflik Keluarga Pada Mahasiswa Program Studi Bimbingan dan Konseling Islam - Nurfajriyah Azani; Ahmad Arifi; Lukman Harahap (Madania: Jurnal Ilmu-Ilmu Keislaman, 2022)
The purpose of this study is to describe the perceptions of Islamic counseling students' perceptions of family conflict in solutions according to the Qur'an. This research is a descriptive field research with qualitative data, researchers use primary data sources in the form of interviews and observations as well as secondary data sources from the results of documentation. Methods of data collection using observation methods, interview methods, and documentation methods. Observational method to observe students' perceptions of family conflict. The interview method was carried out to Islamic guidance and counseling students. The documentation method for documenting everything related to family conflicts. Data validity was carried out using triangulation techniques, cross-checking between observation results, interview results, and documentation methods. The results of the study stated that the factors that influence family conflict are communication, egocentrism, economic problems, busyness problems, educational problems, infidelity problems and far from religion. Meanwhile, the counselor's strategy in resolving family conflicts is by giving free time, communication between 2 parties, understanding problems that occur in society, calm attitude and openness. In problem solving based on Al-Qur'an counseling with several stages, namely introduction and coaching, expressing problems, directing the subject towards Al-Qur'an counseling, namely by following steps: ablution, intention, opening Al-Qur'an, mentadabburi al-qur 'an, activating intuition (dzauq), obtaining guidance (guidance), and sharing opinions with mentors.